The Determinants of Constructive Deviant Behaviour of Frontline Tourism Employees: An Exploration with Perceived Supervisory Support and Intrinsic Motivation - Erenler Tekmen, Esra; Kaptangil, Kerem (Journal of Tourism, Sustainability and Well-being, 2022)
This study examined whether the employees’ internal motivation mediated the relationship between perceived supervisory support and constructive deviance. The population of this study consisted of front-line employees who work at four and five-star hotels in Bolu, Turkey. The study employed simple random sampling, one of the probability sampling methods, and data were collected by survey method. 170 questionnaires were distributed, and the number of valid questionnaires was 154. The analysis of surveys revealed that intrinsic motivation plays a partial mediating role in the relationship between perceived supervisory support and constructive deviance and has a positive significant effect on innovative constructive deviant behaviors. In addition, it was found that positive relationship between supervisory support and challenging constructive deviant behaviours and negative relationship between supervisory support and innovative constructive deviant behaviours. No relationship has been found between supervisory support and interpersonal constructive deviant behaviour. In this context, it should be taken into account that employees should feel the support of managers in order to be more flexible and willing to deal with various situations. The study makes a theoretical contribution to the literature by presenting findings about the antecedents of the tendency of front-line workers in the hospitality industry to exhibit constructive deviant behaviors.